Exploring Content Validity of Shore Handwriting Screening and Newly Developed Score Sheet With Pre-Kindergarten Students - Denise K. Donica; Erin Francsis (Scholarworks @ WMU, 2015)
Background: Limited tools exist to measure handwriting readiness skills of pre-kindergarten students. This study was a preliminary exploration of content validity of the Shore Handwriting Screening (SHS) and the newly developed Score Sheet with the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2) in 4- and 5-year-old pre-kindergarten students. Because socioeconomic status (SES) is known to impact handwriting skills, data from two different socioeconomic groups were collected. Method: Students from a Lower SES group (n = 36) and a Higher SES group (n = 14) completed the SHS and fine motor composite of the BOT-2. Pearson's correlation was used to compare scores on the two assessments within the two groups. Results: SHS overall percentage scores were compared to standard scores and composite scores of the BOT-2. SHS scores displayed moderate to high correlation with fine manual control portions of the BOT-2 for the Lower SES group and low to moderate correlation for the same portion in the Higher SES group. Conclusion: SHS and the Score Sheet correlate to fine and visual-motor skill subtests on the fine manual control portions of the BOT-2, which supports the need for further research on the reliability and validity of the Score Sheet for use in practice.